Brief cognitive therapy for panic disorder: a randomized controlled trial. - Clark, D; Salkovskis, P; Hackmann, A; Wells, A; Ludgate, J; Gelder, M (1999)
Cognitive therapy (CT) is a specific and highly effective treatment for panic disorder (PD). Treatment normally involves 12-15 1-hr sessions. In an attempt to produce a more cost-effective version, a briefer treatment that made extensive use of between-sessions patient self-study modules was created. Forty-three PD patients were randomly allocated to full CT (FCT), brief CT (BCT), or a 3-month wait list. FCT and BCT were superior to wait list on all measures, and the gains obtained in treatment were maintained at 12-month follow-up. There were no significant differences between FCT and BCT. Both treatments had large (approximately 3.0) and essentially identical effect sizes. BCT required 6.5 hr of therapist time, including booster sessions. Patients' initial expectation of therapy success was negatively correlated with posttreatment panic-anxiety. Cognitive measures at the end of treatment predicted panic-anxiety at 12-month follow-up.